A study on factors influencing post- purchase behaviour in E-commerce of young adults in Malaysia - Chan, Chiew Kong (2024)
As e-commerce is experiencing rapid growth with the acceleration from COVID19 pandemic, acknowledging and identifying the consumers' post-purchase behaviour in e-commerce is pivotal. It has shifted the market trend with the rapid advancement of digital technologies and the increasing popularity of online shopping platforms. Hence, understanding the dynamics of post-purchase behaviour has become imperative for businesses aiming to optimize customer satisfaction and loyalty.